Eye donation from palliative and hospice care contexts: the EDiPPPP mixed-methods study - Tracy Long-Sutehall; Mike Bracher; Sarah Mollart; Jane Wale (NIHR Journals Library, 2023)
Background Over 2 million people in the United Kingdom are living with sight loss with costs to the United Kingdom economy reported as £4.34 billion annually. Conditions that lead to sight loss and impaired vision can be treated if eye tissue is available for corneal transplantation, reconstructive surgery and research into eye diseases. Supply of eye tissue (only available via eye donation) is currently insufficient to meet demand; therefore, new routes are needed. Hospice and hospital-based Palliative Care Services have been reported as potential donation sources of this tissue. Objectives To: (1) scope the size and clinical characteristics of the potential eye donation population from research sites; (2) map the donation climate of each research site; (3) identify factors that enable or challenge service providers to consider the option of eye donation from a local and national perspective; (4) identify service users' views regarding the option of eye donation and the propriety of discussing eye donation; and (5) develop and pilot an empirically based intervention designed to change behaviours in relation to eye donation. Design A 36-month mixed-methods, multicentre study undertaking three work packages. Settings Three hospice care and three hospital-based palliative care services situated in the North, Midlands and the South of England (one service of each type per region). Participants Work package 1 - 105 service providers. Work package 2 - 62 service users, and 156 service providers in the national survey. Work package 3 - 21 expert consultees (patient and public involvement, cross discipline). Data sources Scoping review, retrospective note review, qualitative interviews/focus groups, participant observation, secondary analysis of primary data, national survey, transparent expert consultation. Results Potential: The retrospective notes review demonstrated that of 1199 deceased patients' notes, 553 (46%) patients met the criteria for eye donation (56%, n = 337 in hospice care service settings and 36%, n = 216 in hospital palliative care service). Practice: Less than 4% of all cases agreed as eligible for donation had been approached or referred for eye donation. Eye donation is not currently an embedded practice at local and national levels. Perceptions: Service providers were motivated to discuss eye donation but lacked opportunity and capability. Service users were willing and able to hold conversations about eye donation but were not aware of the option and had not had the option discussed with them. Preferences: Service users wanted to be offered the option of eye donation, and service providers wanted bespoke education and training related to eye donation. Evaluation of the developed intervention STEPS - Support Toolkit for Eye donation in Palliative care Settings will follow implementation of the full intervention (expected to begin in October 2022). Limitations Due to the significant impact of the COVID-19 pandemic on clinical sites, partner organisations and national service providers, only two elements of the developed intervention have been pilot tested for proof of concept and the response rate to the national survey was low (8%). Conclusions Significant potential exists for eye donation from hospice care and hospital palliative care services; however, individual and organisational behaviour as well as information system-based changes are needed to maximise this potential. Future work Evaluation of the STEPS - Support Toolkit for Eye donation in Palliative care Settings; Research exploring the wider public knowledge and views regarding eye donation; research exploring the use of language by National Health Service Blood and Transplant-Tissue and Eye Services in their public-facing infographics, communications and campaigns (specifically the use of the term eye donation). Trial registration This trial is registered as ISRCTN14243635: Eye donation from palliative care and hospice care settings. Funding details This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (17/49/42) and will be published in full in Health and Social Care Delivery Research; Vol. 11, No. 20. See the NIHR Journals Library website for further project information. Plain language summary The Royal National Institute of Blind people report that over 2 million people in the United Kingdom are living with sight loss. This number is predicted to double to nearly 4 million by 2050. Conditions that lead to sight loss and impaired vision can be treated if eye tissue is available through, for example corneal transplantation, reconstructive surgery and research into eye diseases. However, the problem is that there is not enough eye tissue available to meet current need. Patients under the care of hospice care services and hospital palliative care services who, due to a cancer diagnosis, are unable to donate other organs or tissues, may be able to donate their eyes. To explore potential for eye donation in these settings, we looked at the clinical notes from patients who died in the previous 2 years to see if they could potentially have been a donor. We also interviewed patients and carers seeking their views regarding 'if', 'when' and 'how' a conversation about eye donation should take place within end-of-life care planning. We also asked healthcare professionals (via interviews and a national survey) about their views regarding eye donation being part of end-of-life planning, and what they saw as the key barriers to this becoming a routine practice. We found that many patients are eligible for eye donation, but very few are asked about this option, and that patients indicated they wanted this option raised with them so that they could make decisions about donation. A review of patient notes, healthcare professional interviews and survey responses indicate that eye donation is not part of the current routine clinical practice. Our work presents a clear case for a change to current practice so that patients who wish to donate are offered this opportunity as a part of routine end-of-life care, and that changes in the current practice require specific training initiatives and institutional support. Scientific summary Background Globally, the estimated number of visually impaired people is reported by the World Health Organization (WHO) to be 285 million, with 39 million individuals recorded as blind, and 246 million as having low vision. According to Pascolini and Mariotti, over 10 million of those reported as blind have bilateral corneal blindness, which could be restored with a corneal transplant. However, these individuals do not have access to sight-saving and sight-restoring transplantation surgery owing to a shortfall in supply of tissue (cornea and sclera) that is only available via eye donation (ED). According to the Royal National Institute of Blind (RNIB), over 2 million people in the UK have sight loss caused by conditions such as keratoconus and Fuchs' corneal dystrophy, which can be treated if eye tissue is available (e.g. by corneal transplantation and reconstructive surgery). Eye tissue is also needed for research into a wide variety of diseases, for example, endothelial failure post cataract surgery. The RNIB reports that approximately 5000 corneal transplants are required annually in the UK to address disease and injury resulting in sight loss, with costs to the UK economy (through unpaid carer burden and reduced employment rates) reported as £4.34 billion annually. Critically, this organisation predicts that by 2050, the number of people with sight loss will double to nearly 4 million in the UK mainly owing to an aging population. It is, therefore, imperative that the tissue needed to intervene in these conditions and to support research into the causes and treatment of eye disease is available. The National Health Services Blood and Transplant (NHSBT) Tissue and Eye Services (TES) Bank in Speke, Liverpool (who supply most eyes for UK surgery) aim to achieve a weekly stock of 350 eyes so that they can provide 70 eyes every working day for treatment or research. From April 2021 to March 2022, donation of eyes from all sources (solid organ donation, tissue donation) generated 4555 eyes from 2286 donors equating to only 13 eyes per day and 88 eyes available per week.